2020
DOI: 10.1016/j.ebiom.2020.102626
|View full text |Cite
|
Sign up to set email alerts
|

Foxf1 knockdown promotes BMSC osteogenesis in part by activating the Wnt/β-catenin signalling pathway and prevents ovariectomy-induced bone loss

Abstract: Background: Forkhead box protein f1 (Foxf1) is associated with cell differentiation, and may be a key player in bone homoeostasis. However, the effect of Foxf1 on osteogenesis of bone marrow-derived mesenchymal stem cells (BMSCs) and ovariectomy-induced bone loss, as well as its clinical implications, is unknown. Methods: By quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and western blotting, we assayed Foxf1 expression in bone tissue, BMSCs, and bone marrow-derived macrophages (BMMs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 49 publications
(34 reference statements)
2
74
0
Order By: Relevance
“…Studies have shown that in people with osteoporosis, bone loss is induced by the reduced bone formation and increased bone resorption 4 , 5 . The bone formation could be modulated by many transcription factors and signaling pathways 6 8 . Therefore, researching the mechanisms that modulate bone formation will be significant for the treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in people with osteoporosis, bone loss is induced by the reduced bone formation and increased bone resorption 4 , 5 . The bone formation could be modulated by many transcription factors and signaling pathways 6 8 . Therefore, researching the mechanisms that modulate bone formation will be significant for the treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitination and degradation of β-catenin are regulated by the balance of GSK-3β and p-GSK-3β [22]. β-Catenin interacts with TCF/LEF-1 or other transcription coactivators in the nucleus and induces the expression of osteogenesis-related molecules to regulate osteogenesis [24,25,47]. Compared with CON-ASCs, DOP-ASCs exhibited relatively downregulated expression of β-catenin, p-GSK-3β, RUNX2, and OPN.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signaling pathway is vital for BMSC differentiation and is a significant pathway for promoting new bone formation, inhibiting bone resorption, and maintaining bone mass [23,24]. In the current study, increased expression of β-catenin, lymphoid enhancing factor-1(Lef-1), and dishevelled-1 (Dvl-1) mRNAs were detected in BMSCs treated with Morusin (0-10 μM) on the 3rd, 5th, and 7th days of differentiation, respectively (Fig.…”
Section: Morusin Promotes Osteogenesis Of Bmscs In Vitromentioning
confidence: 99%